Intercropping of Rotan Manau (Calamus manan), with Rubber (Hevea brasiliensis) - Mohamad, Aminuddin; Mohd. Nor, Nur Supardi (1986)
Rotan manau (Calamus manan) seedlings were planted between rows of rubber (Hevea brasiliensis) trees in a 1.4 ha plantation when the rubber was 13 years old. The relative light intensity (RLI) in the rubber plantation was 50 to 60% measured at midday. Survival of rotan manau at 3 years after planting was 80.6%. The growth rates were variable. The mean stem length was 45.17 ± 32.15 cm. The growth rate is encouraging compared to figures obtained from trials in forest areas.